Design and analysis several band antenna for wireless communication - Nghaimesh, ِAbeer Khalid; Jassim, Ali Khalid; Abid Ali, Waleed Khalid (Bulletin of Electrical Engineering and Informatics, 2023)
This article describes the construction of a dual-band planar monopole antenna. A microstrip patch antenna with a feedline impedance of 50 ohm and a patch composed of G-shaped and inverted L-shaped strips is used to make the suggested antenna ultra wideband for frequencies ranging from 3.1 to 10.6 GHz. In order to design the antennas, we need to know the dimensions 40x40x1.6 mm3 and the thickness of the ground plane (0.035 mm) (5.2 GHz). There is a method of altering the present distribution by introducing slots. the proposed worldwide interoperability for microwave access (WiMAX) and wireless local area network (WLAN) bands, with a peak gain of 5.2% and an omnidirectional radiation pattern, suitable for ultra wide band (UWB) were shown to be viable.